Aplicación de la norma de realización de proteinuria en las gestantes hospitalizadas en el área de gineco-obstetricia del Hospital Teófilo Dávila de enero a junio 2010 - Alvarado Escobar, Elizabeth E. (2011)
The objective of this study consisted in determining the use of the reactive lab. Strip in pregnant women to detect proteinuria. Demographic variables were described. The type of study was descriptive – retrospective, which was carried out in those patients hospitalized in the area of Gineco Obstetrica at the Teófilo Dávila Hospital of Machala. The information was obtained by applying the data collection matrix.